Persepsi Mahasiswa Akuntansi Mengenai Faktor-Faktor Yang Mempengaruhi Pemilihan Karier Sebagai Akuntan Publik Dan Non-Akuntan Publik - Indrayeni (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to determine the perception of accounting students about the factors that affect career selection. In this study, the perceptions of students are measured by the variables of financial reward, professional training, professional recognition, social values, work environment, job market considerations and personality. Data collection in this study was conducted through the dissemination of questionnaires to students majoring in Accounting State University and Private in the City of Padang. The number of samples in this study were as many as 160 respondents. Data analysis in this study using one way anova with the help of SPSS version 21. Instrument data collection using questionnaires with Likert scale that each has been tested and have met the validity and reliability. The results of the analysis show that there are different perceptions of accounting students in choosing careers as public accountants and non-public accountants in terms of financial reward, professional recognition, social values, work environment, job market considerations, and personality. Meanwhile, from professional training factor as a whole there is no difference of perception of accounting student in choosing career as public accountant and non-public accountant. This is because a career in the field of accounting both public accountants and non-public accountants must be accompanied by advance training to make someone professional in carrying out their work. This study is expected to be used as a comparative study for further research and to increase the knowledge and understanding of the accountant's perception of the factors influencing career selection.